(3eNJUQ aj GdUQas ((3GHf MSjf fXGe GdOjf s)
(3ChdgG (B:s
(3hjbhd hgh ScjJ s
(3BNQgG (B:s
(3CHOfi ai ChdGg hBNQg hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3Ydjg Jedcs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdUQas